2016
DOI: 10.15640/jehd.v5n3a17
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among Parents’ Socioeconomic Status, Parental Involvement and Academic Achievement in Taiwanese Middle School Students

Abstract: This historical study addresses the question of inconsistency in the Educational policies of Ghana focusing on the impact on Senior Secondary School Education. It examines the persistent adjustment of Educational reforms witnessed in Ghana whenever there is a change in government. The study acknowledges the frantic efforts made by successive governments since independence to reform the educational system of Ghana to meet the basic requirements to meet the developmental needs of the country. The study traces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…Yukarıda belirtildiği gibi, SES, ebeveyn katılımı ve öğrenci akademik başarısı arasındaki ilişkilerin karmaşık bir yapısı vardır. Bu karmaşık ilişkileri incelemek için, az sayıda çalışma SES ve öğrenci akademik başarısı arasındaki dolaylı ilişkileri incelemiştir (Kung, 2016;Long ve Pang, 2016;Öztürk ve Singh, 2006;Tazouti ve Jarlégan, 2016). Dahası bu karmaşık ilişkiler kültürden kültüre farklılık gösterebilir.…”
unclassified
“…Yukarıda belirtildiği gibi, SES, ebeveyn katılımı ve öğrenci akademik başarısı arasındaki ilişkilerin karmaşık bir yapısı vardır. Bu karmaşık ilişkileri incelemek için, az sayıda çalışma SES ve öğrenci akademik başarısı arasındaki dolaylı ilişkileri incelemiştir (Kung, 2016;Long ve Pang, 2016;Öztürk ve Singh, 2006;Tazouti ve Jarlégan, 2016). Dahası bu karmaşık ilişkiler kültürden kültüre farklılık gösterebilir.…”
unclassified
“…There was no scheduled meeting with the HCP in the adult clinic, and in the few instances where the adolescents were accompanied to the adult clinic, limited communication took place. According to Kung [ 25 ], transferring an adolescent in such manner implies that he or she is unprepared for going to what is likely to be a judgmental, depersonalized and overburdened clinic environment. Although the participants mentioned having good relationships with the HCPs, there was evidence of perceived ineffective bonding that could influence their experience of separation from the pediatric clinic to join the adult clinic.…”
Section: Discussionmentioning
confidence: 99%
“…This is affirmed by other studies globally where similar findings were reported. Others have also reported challenges at transition that include lack of a structured healthcare transition, lack of communication between the pediatric and adult HCPs, mental health problems, strong attachment to the adolescent’s pediatric clinic HCP, privacy/disclosure issues, negative perceptions of the adult clinic HCPs, and stigma [ 17 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the education sector in every country experienced reforms and Adu-Gyamfi, Donkoh, and Adinkrah (2016) noted that reforms in education are attempts to make changes in policy, practices, or organization, or to address an identified issue. Educational reforms help to better the education system and in Ghana, almost every change in political power brings a change to the country"s educational system (Adu-Gyamfi et al, 2016;ICET, 2012). According to Akyeampong (2010), every 5 years Ghana introduces another form of reform.…”
Section: Introductionmentioning
confidence: 99%